Jane Bennett interviewed by Nikki Henningham in the Rural Women of the Year Award oral history project - Bennett, Jane, 1969-; Henningham, Nicola, 1960- (2010)
Jane Bennett talks about her family background; growing up on the family farm; her decision to have a career in farming; her early understanding of gender roles on farms; dairy farming and the low status of the dairy industry in Australia in the 1980s; agricultural class system or heirarchy in Australia; the role of mothers on the farm, their importance to their children's involvement in the local community; social life off the farm, the Deloraine social set in the 1980s; religious diversity of the community; arts culture and the health of regional centres; hippies moving into the area in the 1970s; the importance of the establishment of the Rotary Club Craft Fair; why some rural communities are more successful that others; monocultural farming communities; geographical elements to successful communities and 'Island Culture'; her interest in genetic engineering; her father's decision to become a cheese maker; the start of a cheese factory in Tasmania in the 1980s; studying Dairy Technology at Gilbert Chandler College at Werribee; studying at Kent Business College in England in 2008; women as the agents for change in rural communities; Landcare; Australian rural cultural matters; effectiveness of government policies to change agricultural activity.
Bennett discusses the need for innovation, value adding, marketing and branding of food; Tasmanian economic future; how Tasmanian farmers must adapt to survive; the rate of change required being linked to developments in technology; the importance of the ABC Rural Woman of the Year Award to raising the profile of women; changing attitudes to women in agriculture over the last 15 years; their increased capacity to participate in farming activities; cheese making becoming fashionable by 2005; entering the ABC Rural Woman of the Year Award; the response of the Tasmanian community to her winning the national award; her role in the formation of a Rural Youth Club; her interest in education and training; becoming a delegate on the Rural Industry Training Board, rising to President; working in England, problem solving; the role of Global Communication Technology to the growth of her business; Aldi Supermarkets; the experience of working with people outside agriculture; her application for a Vincent Fairfax Fellowship; opportunities made available and lessons learned through winning the Rural Woman of the Year Award; the importance of service to the community; Nuffield Farming Scholarship; travelling to Taiwan; impact of the feminist movement on people of her age; difficulties associated with the family enterprise for women who want to work in agriculture; her male mentors.
Recorded on 9 February 2010 at Dunorlan, Tas.
Digital master available
Timed summary (6 p.) and uncorrected transcript (typescript, 69 leaves)
Keywords: Bennett, Jane, -- 1969- -- Interviews; Rural Woman of the Year Award; Cheesemakers -- Tasmania -- Interviews; Cheesemaking -- Tasmania; Rural women -- Tasmania -- Interviews; Dairy farming -- Tasmania; Agricultural innovations